Business Opportunities and Agricultural Sustainability in the Future Era of AgriTech - Vinisha Panyala; Uma Bakshi (PT Agung Media Publisher, 2025)
Agriculture faces increasing challenges due to climate change, requiring innovative solutions to ensure sustainability and productivity. AgriTech, encompassing precision farming, AI-driven crop management, and blockchain-based supply chains, offers promising advancements in mitigating climate change effects. However, its adoption remains limited due to economic and infrastructural barriers. This study employs a comparative analysis of AgriTech-based and traditional agricultural methods, utilizing statistical data to assess their effectiveness in addressing climate change challenges. A one-sample t-test was conducted to evaluate the significance of AgriTech interventions, highlighting differences in mean values and confidence intervals. The findings indicate that while AgriTech significantly contributes to climate change adaptation (t = 8.85, df = 49, p < .001), its impact is lower compared to traditional methods due to barriers such as high initial costs and limited access to technology. Despite this, precision agriculture, climate-smart techniques, and blockchain integration demonstrate potential for improving sustainability and efficiency. The study highlights the importance of policy support, financial incentives, and technological literacy in promoting AgriTech adoption. Business opportunities in AgriTech continue to grow, but overcoming adoption challenges requires collaborative efforts from stakeholders, including governments, investors, and farmers. AgriTech has the potential to revolutionize sustainable agriculture by balancing productivity and environmental responsibility. However, further research is needed to explore localized implementation strategies, AI integration, and economic feasibility for smallholder farmers to ensure widespread adoption.